Grit and workplace spirituality on psychological well-being among faculties of higher education institutions - Ali, Amjad; Kumari, Shalu; Ali, Nasir; Sayeeduzzafar, Sayeeduzzafar; Jeet, Vikram (Edelweiss Applied Science and Technology, 2024)
The present research investigates the complex connection between grit, workplace spirituality, and psychological well-being among faculty members in higher education institutions. The study was focused on faculty members of public state universities in India (Bihar). The data was gathered through surveys and then examined using multiple regression analysis. Findings offer valuable insights into the factors that influence psychological well-being among faculty members. Precisely results indicate that grit and workplace spirituality are strong predictors of various aspects of psychological well-being. The study also revealed an interesting facet of workplace spirituality as the workplace spirituality was positively associated with psychological well-being, but a further analysis of its components showed a more complex relationship. The spiritual orientation dimension, representing an individual’s adherence to their spiritual ideals at work, was discovered to adversely affect psychological well-being. This contradictory discovery indicates that an overemphasis on spiritual orientation in higher education could result in a contradiction between personal values and professional requirements, ultimately reducing psychological well-being. It emphasizes the importance of a balanced approach to workplace spirituality that enables individuals to incorporate their spiritual beliefs into their work without facing excessive stress or conflict. The results provide significant information for enhancing the welfare of educational professionals and may have wider significance for the education sector and occupational psychology.